Foreign tourists' evaluation on attractiveness of recreational forests in Peninsular Malaysia as ecotourism destinations - Idris, Nur Hafizah (2014)
As noted in the National Key Economic Area, ecotourism has been identified as an important niche area for Malaysian tourism, effectively differentiating itself from other competing destinations in the region. Conventionally, ecotourism products are developed based on existing cultural and natural attractions. In Malaysia, recreational forests have the potential to be developed and marketed as ecotourism destinations since our forests are endowed with diverse flora and fauna, as well as other natural attractions. There are currently a total of 124 recreational forests in Peninsular Malaysia which receive mostly local visitors and only a handful foreigner.Thus, the principal purpose of this study was to measure the attractiveness of recreational forests as perceived by foreign tourist as ecotourism site. The conceptual framework in this study was constructed based on the model of attitude towards object (ATO), while the attributes listed are based on hierarchy of determinant on attractiveness of forest recreations as presented in several past studies. From the review, 20 characteristics were chosen as representing recreational forest important attributes. Total number of 222 foreign tourists have completed the questionnaire distributed. The main analysis used in this study is mean multiplicative score and importance-performance analysis (IPA). Overall, foreign tourists evaluated recreational forests in Peninsular Malaysia as not quite attractive. From the IPA result, it was found that the most attractiveness attribute is "environmental scenery‟ while "special event‟ was identified as the weakest attractiveness attribute for Malaysian recreational forests. The findings also showed that most of the foreign tourists had not visited recreational forest in Peninsular Malaysia before. Moreover, those who had visited the forests before are less than two times within the previous 12 month. Some said that these forests are not promoted properly and does not perform well in persuading tourists to visit the areas. In general, the findings from this study have provided us an insight on how foreign tourists evaluate the importance and availability of recreational forests in peninsular Malaysia for ecotourism experience. This information is valuable for forest department and tourism agencies for promoting and introducing recreational forests as a new ecotourism product in Malaysia.It is hoped that once the recreational forests were to be developed and promoted as ecotourism sites, they can help to diversify our tourism profile and adding the unique dimension into our ecotourism appeal.